Criminality in context: the psychological foundations of criminal justice reform - Haney, Craig (Psychology, crime, and justice series, 2020)
Individualistic myths and the crime master narrative -- Risks and contexts: an alternative paradigm for understanding criminality -- Criminogenic trauma: social history and the life course -- Institutional failure: state intervention as criminogenic risk -- Criminogenic contexts: immediate situations, settings, and circumstances -- Poverty: structural risk and criminal behavior -- The criminogenics of race in a divided society: racialized criminality and biographical racism -- Individualistic myths and the disregard of context: deconstructing "equally free autonomous choice" -- Reorienting the law: context-based legal reforms -- Pursuing social justice: an agenda for fair, effective, and humane crime policy.